E-banking, Fintech, & Financial Crimes: The Current Economic and Regulatory Landscape - Gupta, Chander Mohan; Kaur, Gagandeep (Springer Nature Switzerland, 2024)
1. Fintech Revolution: Navigating Consumer Privacy Concerns and Cybersecurity Challenges -- 2. Fintech Landscape -- 3. Fintech in International Relations – some reflections on globalization and transnational governance -- 4. Theoretical Prespective of Fintech -- 5. The role of Fintech on creative accounting and companies’ performance -- 6. DEMYSTIFYING THE DEMAND AND SUPPLY OF MONEY IN INDIA -- 7. Financial Crimes through Fin Tech by Political Leaders: The Experience of Select South Asian States -- 8. FINANCIAL CRIMES AND FINTECH IN INDIA -- 9. Financial Crimes in Fintech: An Evidence from Cryptocurrency Market -- 10. Compliance related to Fintech: An overview of India legal system -- 11. Optimizing the Role of Indonesian Fintech and Legal Protection Efforts for Fintech Users by the Indonesian Financial Services Authority (OJK) in Financial Services -- 12. Legal Implications of Fintech -- 13. DECENTRALIZED FINANCE (DEFI) AND LEGAL CHALLENGES: NAVIGATING THE INTERSECTION OF INNOVATION AND REGULATION IN THE FINTECH REVOLUTION.